Assessing the Alignment and Implementation Challenges of the Sustainable Development Goals (SDGS) 2030 in Morocco: A Relevant Inquiry - Chehbouni , Ghita (Journal of Sustainable Development Law and Policy, 2025)
Morocco, a North African nation known for its rich cultural heritage and diverse landscapes, has been actively pursuing the Sustainable Development Goals (SDGs) as a framework to guide its development efforts1 . The country has made significant progress in aligning its national development strategies with the SDGs, particularly prioritizing goals such as quality education2 , clean water and sanitation, and clean energy3 . This paper aims to evaluate the effectiveness of SDGs implementation in Morocco, highlighting achievements, challenges, and future prospects. (Smith, 2020). The SDGs, adopted by the United Nations in 20154 , represent a global commitment to address pressing challenges including poverty, inequality, climate change, environmental degradation, peace, and justice. This review provides an analysis of the SDGs’ effectiveness in driving positive change across various dimensions5 . By examining academic literature, reports, it evaluates progress towards achieving the SDGs, identifies key implementation challenges, and assesses potential for successful realization. The article explores how effectively Morocco aligns its policies and addresses implementation challenges to achieve the SDGs by 20306 , considering factors such as cultural diversity, economic structures, and geographic disparities. The integration of the SDGs into Morocco’s development agenda presents both challenges and opportunities. By addressing issues like adaptation, inter-sectoral coordination, data availability, climate resilience, and policy integration, Morocco seeks to overcome these challenges. Understanding these obstacles and their solutions is crucial for assessing the relevance and effectiveness of SDGs’ implementation, ultimately contributing to Morocco’s sustainable development journey by 2030.